Military cultures and martial enterprises in the Middle Ages : essays in honour of Richard P. Abels - Hosler, John D.; Isaac, Steven; Abels, Richard Philip, 1951- (The Boydell Press, 2020)
"The essays in this volume honour the career and achievements of Richard Abels, the distinguished historian of medieval military history; in particular, they aim to reflect how the "cultural turn" in the field has led to exciting new developments in scholarship. Ranging from the late eighth century to the fifteenth, from northern England to the Levant, the chapters analyze how medieval kings and commanders practiced a genuine military science, how the meanings of victory and defeat were constructed by chroniclers and whole societies, how wars were remembered and propagandized, and how religion and war mixed"--